Islamic Spiritual Practice as a Pathway to Psychological Well-being: Evaluating the Impact of Devotional Remembrance (Dhikr) on Stress - Sufya, Dina Haya (LPPM Universitas 17 Agustus 1945 Samarinda, 2025)
Dzikir therapy (Islamic mindful prayer) is a psychospiritual approach believed to alleviate stress and enhance psychological well-being. However, empirical studies on the efficacy of dzikir in reducing stress among adolescents remain limited. This study aimed to evaluate the effect of dzikir therapy on stress levels in university students using an experimental design supplemented by post-intervention interviews. A pretest-posttest control group design was implemented with 28 participants randomly assigned to experimental and control groups. The intervention involved daily individual dzikir practice for 30 minutes over two weeks. The Perceived Stress Scale (PSS-10) was administered to collect quantitative data, while post-experiment interviews provided qualitative insights. Quantitative data were analyzed using independent samples t-tests, and qualitative data were thematically analyzed. Results indicated a significant reduction in stress scores for the experimental group compared to the control group (p = .022, d = 1.03). Qualitative findings revealed that dzikir helped participants manage negative emotions, strengthen spiritual connectedness, and cultivate reflective, positive thinking patterns. The study concludes that dzikir therapy demonstrates statistical and phenomenological effectiveness in reducing stress among adolescents, supporting its integration into holistic stress management interventions